EXTENSION OF LIMITED STAY PERMIT FOR MALAYSIAN FOREIGN EMPLOYEE AT PT. SEFONG INDUSTRIES - Wilson Reinaldo; Shenti Agustini (ConCEPt - Conference on Community Engagement Project, 2022)
Job Training Program is designed as a form of learning that is integrated with the implementation of academic collaboration for community service. The form of cooperation is carried out in the form of assistance in providing solutions, creating certain innovations and technologies in a comprehensive and sustainable manner. By looking at the needs of several companies in hiring foreign employees to support the running of their companies and with the complexity of the main requirements in hiring expatriate, which is to have a Limited Stay Permit Card (KITAS) which causes the company to have difficulty in the process of hiring foreign employees, the author decided to provide assistance in the form of the process of extending the Limited Stay Permit Card (KITAS) document. Another problem that is also faced is the change of employees who take responsibility for carrying out each renewal process every year which leads to confusion experienced by personnel (Department of Human Resources) motivating the author to solve this problem by making a manual as a guide for personnel to carry out the process of extending the Limited Stay Permit Card (KITAS). The extension process will be carried out by completing the requirements through the government's official website which will then be ratified after going through the approval and payment process in three stages starting from RPTKA, Notification to the Immigration stage. The entire filling process will be documented so that a manual can be made at the end of the Job Training Program.